Learning mathematics using drill and practices based on augmented reality (AR) / Nik Rosmawani Nik Mat - Nik Mat, Nik Rosmawani (2017)
Mathematics subject is one of the most important subjects to learn from pre-school until university or until whole life. Mathematics is one of the subject are difficult to understand and learning moreover in remembering formula. Using the traditional teaching method such as teach in classroom and reference book, does not help students to understand better. However, without a variety of choose and interactive learning, they can only feel boring and not understand. Thus, this project presents an interactive application that is design to help students in learning Maths better whether at class and at home environment. Using a new trend and technology that are widely used nowadays which is Augmented Reality (AR) technique is proposed in learning Maths. The Scaffolding technique is used in learning Mathematics in order to help students learn Mathematic. Then, an interactive gaming concept are used to help students in understanding the Mathematic subject effectively. The application proposed is developed by computer-based technology for interactivity. Learnability of an application of students will be measured. Based on the testing conducted, result show that the application is effective. As a conclusion, this paper will help students in learning Mathematics.